1985
DOI: 10.1111/j.1365-2621.1985.tb10541.x
|View full text |Cite
|
Sign up to set email alerts
|

Gel Strength Development During Heating of Surimi in Combination with Egg White or Whey Protein Concentrate

Abstract: Gel strengths (work of penetration) of surimi (refined minced fish, MF) alone and in combination with egg white or whey protein concentrate were periodically measured by an annular pump during constant rate heating. Combination gels containing low percentages of MF were of a lesser strength than an additive relationship would have predicted. However, the strength of gels containing greater percentages of MF did relate to the gel strengths of the uncombined proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
1
19
0
2
Order By: Relevance
“…To reduce cost, improve flavor, and/or enhance texture of meat products, a number of additives have been developed and used in meat products, including enzymes as well as protein and nonprotein additives. These functional protein additives have been examined: whey (Burgarella and others 1985a, 1985b; Weerasinghe and others 1996; Liu and others 2000), caseinate (Camou and Sebranek 1990), egg albumen (Burgarella and others 1985a, 1985b; Hamann and others 1990; Pietrasik and Li‐Chan 2002), soy (Kurth and Rogers 1984; Feng and others 2003; Ramírez‐Suárez and Xiong 2003), wheat gluten (Ramírez‐Suárez and others 2005), cereal proteins (Chang‐Lee and others 1990; Chung and Lee 1990), and blood plasma and globin proteins (Autio and Mietsch 1990; Park 1994; Kang and Lanier 1999; Lou and others 2000). In addition, these nonprotein additives have been used in surimi and other meat products especially restructured meats; starch (Chen and others 1993; Yoo and Lee 1993; Yoon and others 1997a, 1997b; Kong and others 1999a, 1999b, 2001) and hydrocolloids such as carrageenan, alginate, pectins, xanthan gum, locust bean gum, and guar gum (Gómez‐Guillén and others 1997; Montero and others 2001; Pérez‐Mateos and others 2001; Barrera and others 2002; Ramírez and others 2002; Verbeken and others 2005).…”
Section: Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce cost, improve flavor, and/or enhance texture of meat products, a number of additives have been developed and used in meat products, including enzymes as well as protein and nonprotein additives. These functional protein additives have been examined: whey (Burgarella and others 1985a, 1985b; Weerasinghe and others 1996; Liu and others 2000), caseinate (Camou and Sebranek 1990), egg albumen (Burgarella and others 1985a, 1985b; Hamann and others 1990; Pietrasik and Li‐Chan 2002), soy (Kurth and Rogers 1984; Feng and others 2003; Ramírez‐Suárez and Xiong 2003), wheat gluten (Ramírez‐Suárez and others 2005), cereal proteins (Chang‐Lee and others 1990; Chung and Lee 1990), and blood plasma and globin proteins (Autio and Mietsch 1990; Park 1994; Kang and Lanier 1999; Lou and others 2000). In addition, these nonprotein additives have been used in surimi and other meat products especially restructured meats; starch (Chen and others 1993; Yoo and Lee 1993; Yoon and others 1997a, 1997b; Kong and others 1999a, 1999b, 2001) and hydrocolloids such as carrageenan, alginate, pectins, xanthan gum, locust bean gum, and guar gum (Gómez‐Guillén and others 1997; Montero and others 2001; Pérez‐Mateos and others 2001; Barrera and others 2002; Ramírez and others 2002; Verbeken and others 2005).…”
Section: Additivesmentioning
confidence: 99%
“…Burgarella and others (1985b) reported that egg white and whey protein substitutions interfered with fish protein gelation in surimi. The energy levels required to penetrate the fish + egg white and fish + whey gels were lower than those required for individual protein gels.…”
Section: Additivesmentioning
confidence: 99%
“…This was probably because these nonmuscle proteins interfered with gel formation by preventing actomyosin cross‐linking (Chung and Lee 1991). Burgarella et al. (1985) suggested that loss of gel strength with nonmuscle protein additives could be caused by “dilution” of myofibrillar protein.…”
mentioning
confidence: 99%
“…Those researchers concluded that egg white does not interfere with the interaction between myosin molecules. Conversely, egg-white solutions added to surimi (Atlantic Croaker) were antagonistic to gel formation (Burgarella et al, 1985b). Clark et al (1983) identified an interference of gel network formation in model mixtures of agar and gelatin.…”
Section: Resultsmentioning
confidence: 98%